The role of government funding in the development of small enterprises from the viewpoint of their owners ( Tartous model) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research is a field study of the reality of government funding for small enterprises (Tartous model) and aims to identify the role played by the state in the development of these enterprises from the standpoint of their respective owners.And based on a sample of citizens have benefited from government financing services in order to stand on the importance of the role of such funding in the development and support of small businesses Answers, it was reached the following conclusions:1.   No one contributes to government funding to increase the percentage of those wishing to obtain loans for the establishment of small enterprises.2.   No effect of government funding to support the continuity of small enterprises.3.    There is no effect of government funding to support the continuity of small enterprises.4.   The need for many of the sources of funding as well as a source of government funding.At the end of the research was to formulate a set of recommendations aimed at achieving the maximum benefit from government funding for small enterprises in order to improve the economic situation of workers in these enterprises. دور التمويل الحكومي في تنمية المشروعات الصغيرة من وجهة نظر أصحابها (محافظة طرطوس نموذجاً ) يعد هذا البحث دراسة ميدانية لواقع التمويل الحكومي للمشروعات الصغيرة (محافظة طرطوس نموذجاً) ويهدف إلى التعرف على الدور الذي تقوم به الدولة في تنمية تلك المشروعات من وجهة نظر أصحابها. و يعتمد على إجابات عينة من مواطنين استفادوا من خدمات التمويل الحكومي بغية الوقوف على أهمية دور هذا التمويل في تنمية ودعم المشروعات الصغيرة،  وتم التوصل إلى الاستنتاجات الآتية: 1-  لا يساهم التمويل الحكومي في زيادة نسبة الراغبين بالحصول على قروض لإنشاء مشروعات صغيرة. 2-  لا يوجد تأثير للتمويل الحكومي في دعم استمرارية المشروعات الصغيرة. 3-  لا يوجد تأثير للتمويل الحكومي في دعم استمرارية المشروعات الصغيرة. 4-  الحاجة إلى العديد من مصادر التمويل بالإضافة إلى مصدر التمويل الحكومي. وفي نهاية البحث تم صياغة مجموعة من التوصيات الهادفة إلى تحقيق الاستفادة القصوى من التمويل الحكومي للمشروعات الصغيرة في سبيل تحسين الواقع الاقتصادي للعاملين في تلك المشروعات.